Emulsion stability and microwave demulsification of crude oil emulsion - 254730 Abdurahman Hamid Nour; Mohd. Ariffin Abu Hassan, supervisor (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Doctor of Philosophy) - Universiti Teknologi Malaysia, 2006